Covid-19 scenario in india - a review - D, Rajesh Babu (Journal of Management and Science, 2022)
In India, covid-19 has had a huge and negative impact on the Indian Economy. Various sectors affected and lost revenues from the last two years. Coronavirus created a massive gap for business entities, and most of the organizations, state government, and the central government lost the revenue. The purpose of the study is to focus on problems and issues related to covid-19 in Indian to provide necessary recommendations. Secondary data method selected for carrying research work. The article covered tourism,transportation, aviation, media and entertainment, pharma. Other related aspects are government monetary policy activity and RBI financial assistance to the Indian Economy.